Smart Dairy Cattle Farming and In-Heat Detection through the Internet of Things (IoT) - Arago, Nilo; Robles, Rodney Rafael; Alvarez, Chris; Mabale, Angelita; Legista, Charl; Repiso, Nicole; Amado, Timothy; Jorda, Romeo Jr.; Thio-ac, August; Tolentino, Lean Karlo; Velasco, Jessica (International Journal of Integrated Engineering, 2022)
The Internet of Things (IoT) technology has been being revolutionized in various aspects of agriculture around the world ever since. Its application has already found its success in some countries. On the contrary, this technology has yet to find its substantial breakthrough in the Philippines. This study shows the application of IoT in improving the detection efficiency of standing-heat behaviors of cows through automated detection using Pan-tilt-zoom cameras and a Python-driven Web Application. The dimensions of the barn were measured, and the Cameras' Field of Views (FOVs) were pre-calculated for the strategic positions of the cameras atop of the cowshed. The program detects the cows and any estrus events through the surveillance cameras. The results will be sent to the cloud server to display on the web application for analysis. The web app can allow updates on cow information, inseminations, pregnancy, and calving records, estimate travel time from the user's geolocation to the farm, provide live monitoring and remote camera accessibility and control through the cameras and deliver reliable cross-platform push-notification and call alerts on the user's device(s) whenever an estrus event is detected. Based on the results, the program performed satisfactorily at 50% detection efficiency.